Resistance to pathogens in terpene down-regulated orange fruits inversely correlates with the accumulation of D-limonene in peel oil glands - Rodriguez, Ana; Shimada, Takehiko; Cervera, Magdalena; Redondo, Ana; Alquezar, Berta; Rodrigo, María J.; Zacarias, Lorenzo; Palou, Lluís; López, María M.; Pena, Leandro (2017)
Volatile organic compounds (VOCs) are secondary metabolites acting as a language for the communication of plants with the environment. In orange fruits, the monoterpene D-limonene accumulates at very high levels in oil glands from the peel. Drastic down-regulation of D-limonene synthase gene expression in the peel of transgenic oranges harboring a D-limonene synthase transgene in antisense (AS) configuration altered the monoterpene profile in oil glands, mainly resulting in reduced accumulation of D-limonene. This led to fruit resistance against Penicillium digitatum (Pd), Xanthomonas citri subsp. citri (Xcc) and other specialized pathogens. Here, we analyze resistance to pathogens in independent AS and empty vector (EV) lines, which have low, medium or high D-limonene concentrations and show that the level of resistance is inversely related to the accumulation of D-limonene in orange peels, thus explaining the need of high D-limonene accumulation in mature oranges in nature for the efficient attraction of specialized microorganism frugivores.